THE USE OF SONG LYRICS IN IMPROVING STUDENTS' GRAMMAR MASTERY OF PAST TENSE : A quasi-experimental study at the second grade of one senior high school in - Mega, - (2011)
This study was aimed at investigating the use of song lyrics in improving students' grammar mastery of past tense at senior high school students. This study used quasi experimental design. Two classes of the second graders at a senior high school in Cianjur were selected purposively as the sample. The data were obtained through a pre-test, a post-test and open ended questionnaire. The findings were analyzed statistically using independent t-test, dependent t-test procedure and analyzed questionnaire descriptively. The statistical computation showed that the use of song lyrics was likely to be effective in improving the students' grammar mastery of past tense (tobt 2.831 > tcrit 2.000, r = 0.348) and the result of dependent t-test (0.00 > 0.05). Furthermore, the factor that influenced the effectiveness of the use of song lyrics was also supported by students' responses in the questionnaire. Most of students gave positive responses to the use of song lyrics in improving their grammar mastery of past tense. The use of song lyrics gave some advantages: making students easier to memorize the verbs and understand the grammar, making students more enthusiastic, and creating better atmosphere in the class. Besides, students get new vocabulary and know how to pronounce the verbs. Appropriately, the research is expected to give a contribution to the teaching of English especially in teaching grammar.